Sekolah Mode Di Pekanbaru Dengan Pendekatan Arsitektur ART Deco - Maulida, Syadzwana; Amanati, Ratna; Rijal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Fashion school in Pekanbaru is a place of informal education in the field of fashion based Institute of Vocational Education. Fashion is a style that can be expressed through fashion products, so that the same thing happened to the art deco movement that produces an object related to one of the fashion products. Art deco architecture appears as a result of the global changes that produce the trend in expressing of shapes and a new spirit of expression. Base on that, then has decided "Streamline Dynamic" as be a concept of design. Design of fashion school used the characteristic of "streamline deco" approach based on the principle C.R Wolff Schomaker and A.F. Aalbers, who was brought to Indonesia due to environmental conditions and climate adjustment. The application concept of fashion school are on the zoning pattern, form of mass, landscape, fasade of building, and interior. The result of streamline chararacteristic approach on design of fashion school are: adjustment to the environment at zoning, orientation in the form of line hyrarchy in form of mass, the form adoption of the order of mass from the direction of orientation. The establishment of the landscape and interior are applying pattern of form a strict lines dynamic with bright colors. Then, the application form of the mass and fasade using geometric in the form of pattern.Keyword: Fashion School, Fashion, Streamline Dynamic, Architecture Art Deco